2007
DOI: 10.3390/12040842
|View full text |Cite
|
Sign up to set email alerts
|

Identificationof Major Phenolic Compounds of Chinese Water Chestnut and their Antioxidant Activity

Abstract: Chinese water chestnut (CWC) is one of the most popular foods among Asian people due to its special taste and medical function. Experiments were conducted to test the antioxidant activity and then determine the major phenolic compound components present in CWC. CWC phenolic extract strongly inhibited linoleic acid oxidation and exhibited a dose-dependent free-radical scavenging activity against alpha,alpha-diphenyl-beta-picrylhydrazyl (DPPH) radicals, superoxide anions and hydroxyl radicals, which was superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
(33 reference statements)
0
36
0
Order By: Relevance
“…The results obtained for water chestnut at a concentration of 50 mg/mL in methanol, ethanol, and aqueous solution are 45.64%, 35.08%, 30.52%, respectively, which are comparable to that of standard BHT (61.84%) at the same concentration. The inhibition of lipid peroxidation may be due to the presence of phenolics in the extract and it has also been previously reported by Yanli et al (2007) in the case of Chinese water chestnut.…”
Section: Lipid Peroxidationmentioning
confidence: 89%
See 1 more Smart Citation
“…The results obtained for water chestnut at a concentration of 50 mg/mL in methanol, ethanol, and aqueous solution are 45.64%, 35.08%, 30.52%, respectively, which are comparable to that of standard BHT (61.84%) at the same concentration. The inhibition of lipid peroxidation may be due to the presence of phenolics in the extract and it has also been previously reported by Yanli et al (2007) in the case of Chinese water chestnut.…”
Section: Lipid Peroxidationmentioning
confidence: 89%
“…Hydroxyl radical scavenging ability of extracts denotes that it is a good scavenger of reactive oxygen species. Yanli et al (2007) also reported the hydroxyl scavenging activity of Chinese water chestnut at a concentration of 50 µg/mL.…”
Section: Antioxidant Activity Against Oxidative Damage To Dnamentioning
confidence: 99%
“…Fresh-cut CWC contains tyrosine, gallic acid, chlorogenic acid and 2,4-dihydroxy-cinnamic acid during the early days of storage (Tong, 2005). In addition, fresh-cut CWC contains phenolic compounds, mainly dopa and epicate (Pan & Chen, 2008), but only at low concentration (You et al, 2007). However, neither of them can be detected in the subsequent storage period.…”
Section: Introductionmentioning
confidence: 98%
“…Consumption of fruits and vegetables by human beings, shown lower risk of chronic diseases such as cancer, cardiovascular disease and stroke 1 and positive health effects 2 due to high contents of certain phenolic compounds in plant-derived foods. Recently, phytochemicals and their effects on human health have been intensively studied.…”
Section: Introductionmentioning
confidence: 99%